2016
DOI: 10.15294/kreano.v7i1.5001
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Matematika Dengan Strategi TTW Berbasis Learning Journal untuk Meningkatkan Kemampuan Menulis Matematis

Abstract: Kreano 7 (1) (2016): 58-65 Ju r n a l M a t e m a t i k a K r e a t i f -I n o v a t i f http://journal.unnes. Teknik pengumpulan data menggunakan teknik tes kemampuan menulis matematis dan observasi untuk memperoleh data pengamatan. Teknik analisis data untuk menilai kevalidan perangkat pembelajaran dilakukan oleh 5 validator dengan menggunakan instrumen lembar validasi perangkat pembelajaran. Kepraktisan dan keefektifan perangkat pembelajaran dianalisa setelah uji coba perangkat pada kelas yang diajar den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The TTW strategy (Think-Talk-Write) was first introduced in 1996 by Huinker and Laughlinn (Suyanto, 2016). The TTW strategy, according to its name, has three steps or activities, namely (1) Think, (2) Talk, and (3) Write (Afthina & Pramudya, 2017).…”
Section: Theoretical Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The TTW strategy (Think-Talk-Write) was first introduced in 1996 by Huinker and Laughlinn (Suyanto, 2016). The TTW strategy, according to its name, has three steps or activities, namely (1) Think, (2) Talk, and (3) Write (Afthina & Pramudya, 2017).…”
Section: Theoretical Supportmentioning
confidence: 99%
“…In this study, researchers tried to compare the RQA strategy with the TTW strategy to overcome the low concepts understanding of junior high school students. Several previous studies reveal that the TTW strategy can overcome the students' difficulties in problem-solving, learning outcomes, and mathematical writing skills (Nurjanah & Poernomo, 2018;Sopiany & Hijah, 2016;Suyanto, 2016). Meanwhile, the RQA strategy has also succeeded in overcoming students' low learning outcomes, mastery of learning, criticalthinking skills, and students' metacognition (Maulida et al, 2017;Nuzulah & Budijastuti, 2018;Sumampouw, 2011;Thalib, Corebima, & Ghofur, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The branch of science that uses logic and is universal can play a role in developing modern technology known as mathematics. Learning mathematics includes several things, namely: the ownership of values and attitudes, understanding concepts, and the ability to apply them in everyday life [1]- [3] [4]. Mathematics has been applied at all education levels to solve a problem logically, analytically, critically, and creatively [6]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…This Think Talk Write (TTW) model has been applied by [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] from the study the Think Talk Write (TTW) model has a significant effect on the results and student learning activities. Based on the explanation, it can also be concluded that the Think Talk Write (TTW) model is well used to train students' thinking well.…”
Section: Introductionmentioning
confidence: 99%